1992
DOI: 10.1063/1.107191
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystalline, epitaxial cubic SiC films grown on (100) Si at 750 °C by chemical vapor deposition

Abstract: Single-crystalline, epitaxial cubic (100) SiC films have been grown on (100) Si substrates at 750 °C by low-pressure chemical vapor deposition, using methylsilane, SiCH3H3, a single precursor with a Si:C ratio of 1:1, and H2. This epitaxial growth temperature is the lowest reported to date. The films were characterized by means of transmission electron microscopy, x-ray diffraction, infrared transmission, four-point probe and other methods. Based on double-crystal x-ray diffractometry, the crystalline quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(72 citation statements)
references
References 5 publications
1
71
0
Order By: Relevance
“…This is a standard observation in non-catalytic thin film deposition techniques (MBE, PVD, CVD ) that the crystalline quality of the film decreases with decreasing deposition temperature and increasing precursor supply [37,38]. This behavior is usually attributed to the kinetic competition between the supply of the gaseous precursor and the rearrangement of the surface intermediates.…”
Section: Modelingmentioning
confidence: 99%
“…This is a standard observation in non-catalytic thin film deposition techniques (MBE, PVD, CVD ) that the crystalline quality of the film decreases with decreasing deposition temperature and increasing precursor supply [37,38]. This behavior is usually attributed to the kinetic competition between the supply of the gaseous precursor and the rearrangement of the surface intermediates.…”
Section: Modelingmentioning
confidence: 99%
“…The samples grown on the carbonized layers formed by method 1 are characterized by a rougher surface morphology, smaller terrace width, and exhibit a smaller interface width and full width at half maximum of the (111) SiC XRD peak (FWHM). The observed values measured in the q-2q scan are better than the values obtained for films with similar thickness grown by solid source MBE [4] and gas source MBE [43], are comparable with values reported for thicker layers grown by solid source molecular beam epitaxy [13] and are better than the values obtained in the case of low [8,9,44] and high [45] temperature CVD. The larger roughness on layers with C-faces might be an evidence for the different incorporation mechanisms of the deposited atoms and the smaller surface diffusion length compared to the Si-face.…”
Section: Hydrogen Poor and Rich Carbonization Environmentsmentioning
confidence: 40%
“…For this reason most research is focused to improve the crystallographic properties and reduce the residual stress of the SiC layer. This can be achieved by using one of the following substrate modification methods: 1. reduction of the growth temperature by using high reactive carbon precursor and/or atomic layer epitaxial techniques [4][5][6][7][8][9][10][11][12][13][14], 2. use of silicon on insulator substrates [15], 3. application of SMART-CUT or wafer bonding technologies [16][17][18], 4. use of porous and nanostructured silicon [18][19][20], 5. modification of the silicon substrate with group IV elements [21][22][23][24]. Only the latter method is applicable if the electrical properties of the heterojunction are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the successful epitaxial growth of SiC films has been carried out by chemical vapor deposition (CVD) technique using silane, propane, and hydrogen [3]. Golecki et al first reported that a CVD technology using methylsilane (CH 3 SiH 3 ) was useful for the growth of SiC on Si [4]. Subsequent various studies [5][6][7][8][9][10][11][12][13][14][15][16][17] also succeeded in producing SiC films on Si using various deposition methods with methylsilane.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent various studies [5][6][7][8][9][10][11][12][13][14][15][16][17] also succeeded in producing SiC films on Si using various deposition methods with methylsilane. In those studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17], methylsilane was selected as a gas source because the methylsilane molecule has a Si-C bond and its stoichiometric composition (atomic concentration ratio of Si to C) is the same as that of SiC. On the other hand, Xu et al reported that the dissociative adsorption of methylsilane onto the Si surface broke the Si-C bond [18].…”
Section: Introductionmentioning
confidence: 99%